Work in progress - Serious 3D game for mobile networks planning (2010)
Serious games is an emerging technology growing in importance for specialized training, taking advantage of 3D games and game engines in order to improve the realistic experience of users. The concept of a serious game combines the concept of computer games used for recreational purposes with specific goals like training specialized personnel and is part of the concept of blended learning. The idea of a serious game for radio planning requires some level of abstraction and a combination between visual designers and engineers in order to maintain accurate concepts about radio and a good "feeling" from the gamer or user side. In this paper we expose the development of a serious game for Telecommunications planning training, which uses open source tools and real data from Digital Terrain Maps. We combine some innovative ideas about propagation models, 3D modeling of digital terrain, game engines and a traditional radio planning too